Using survey data to estimate the prevalence of Diabetes in South Africa - from risk factor analysis to action - Klein, Murray (School of Economics, 2025)
South Africa is a developing country which has in the last decades experienced a sharp rise in the number of diagnosed diabetes cases. Significant uncertainty exists about the true prevalence of diabetes in South Africa, since many of those suffering from diabetes remain undiagnosed. The large financial burden imposed by diabetes on the public health sector places significant pressure on its ability to effectively deliver quality healthcare to all who rely on it. The Indian Diabetes Risk Score (IDRS) was developed as a low-cost screening tool to assess the potential undiagnosed case prevalence of type 2 diabetes using analysis of risk factors and their association to diabetes. The South African General Household Survey (SAGHS) (StatsSA, 2021a) is used to analyse the risk factors of diabetes on a population through a generalised linear regression model. A synthetic IDRS was calculated from the available population trends and an illustrative prediction of the diabetes prevalence rate was performed using this score. The IDRS could be modified and used in South Africa to model undiagnosed cases of diabetes. Furthermore, the IDRS would allow for government screening to be targeted, thereby allowing for the potential healthcare cost savings.